Mental health status of unmarried youth living in single parent families: a case study from India. (4th July 2019) - Sinha, Atreyee; Ram, Faujdar
Abstract: Background : In South Asian countries like India, family system lays a strong foundation in societies and therefore, the context and consequences of single parent family structures are markedly different from that of the West. In these societies single parenthood is mainly an outcome of untimely death of any one of the parents. Aims : This study tried to examine the influence of parents' survival status on the mental health of youth in India. Methods : "Youth in India: situation and Needs (2006–2007)" survey data was used in the present study. We compared two groups of unmarried young population aged 15–24 y ( n  = 28 637): one having both parents alive and another having only one parent alive. Bivariate and multivariate techniques were applied to analyze the data. Results : Results revealed that around 11% of the unmarried youth belonged to single parent families. Findings underscored a significant association between parent's survival and mental health of youth; respondents from single parent families were more likely to report metal health problems Moreover, effects of parents' survival were significant on females' mental health rather than males'. Conclusion : Policies must focus on reducing stress of young people growing up in single parent families through enhanced educational and employment opportunities.